Yaqtin dalam perspektif Islam dan sains: Telaah kisah Nabi Yunus AS dan manfaat kesehatannya - Cantika, Dhewanti Puspa; Salsabila, Syawaluna Ghefira; Amiruddin, Muhammad; Hanifah, Dewi (Maliki Interdisciplinary Journal, 2025)
The fruit yaqtīn (Cucurbita moschata) holds significance in both Islamic tradition and modern science. In the Qur'an (As-Saffāt 37:146), Allah caused a gourd tree to grow to protect and heal Prophet Yunus (AS), symbolizing divine care and recovery. Hadith also notes the Prophet Muhammad’s preference for gourd as a nutritious food, reinforcing its traditional value. Ethnobotanical records show C. moschata is used across Southeast Asia, the Americas, India, China, and Brazil for treating various conditions—antiparasitic, antidiabetic, anti-inflammatory, hepatoprotective, and energy-boosting purposes. Phytochemical studies reveal it contains carotenoids (β-carotene, lutein), vitamins A, C, E, polyphenols, saponins, phytosterols, and bioactive peptides. These compounds act as antioxidants, immunomodulators, and enzyme inhibitors (α-amylase, α-glucosidase, COX-2), with effects supported by in vitro and in vivo studies showing hypoglycemic, analgesic, and antifatigue properties. While laboratory findings are promising, human clinical data remain limited. This paper explores yaqtīn’s scriptural and empirical relevance, highlighting its potential as a holistic nutraceutical that bridges spiritual wisdom and modern evidence. Future research should focus on clinical trials, dosage standardization, long-term safety, and pharmaceutical formulation for integration into modern therapeutics.